Feasibility Analysis of the Wind Energy Potential in Libya using the RETScreen Expert - Kassem, Youssef; Camur, Huseyin; Mosbah, Almonsef Alhadi Salem (Engineering, Technology & Applied Science Research, 2023)
This study focuses on the evaluation of the economic viability of various scale wind farms and the assessment for the first time of the wind power potential of 22 locations distributed over Libya. The study utilizes monthly mean wind data collected from the NASA power dataset. The analysis includes determining and analyzing the mean wind speed, frequency distribution, and Weibull distribution scale and shape factors. The results showed that Darnah is the most promising location for insulation wind farms due to the high value of wind speed. Moreover, RETScreen software is used to estimate the energy output and conduct an economic feasibility analysis of the wind farm. Additionally, this paper establishes a relationship between the wake effect, airfoil losses, and the potential for greenhouse gas (GHG) mitigation and the performance of wind farms. The results indicate that wind projects are economically viable when the EWT-DW 52 with a capacity of 500 kW is used. The study findings show that the wake effect is a crucial consideration in wind farm design, and it can be minimized through strategic spacing and turbine design. Furthermore, the accumulation of dirt and debris on wind turbine blades can significantly reduce a wind farm’s energy output, causing turbine inefficiency and decreasing the overall energy production. Additionally, the energy production cost from a wind farm is less than that of the electricity tariff and can result in a profitable wind energy project.